Conditional survival of patients with small renal masses undergoing active surveillance. (27th August 2018) - Petros, Firas G.; Venkatesan, Aradhana M.; Kaya, Diana; Ng, Chaan S.; Fellman, Bryan M.; Karam, Jose A.; Wood, Christopher G.; Matin, Surena F.
Abstract : Objectives: To determine conditional survival for patients with small renal masses (SRMs) undergoing active surveillance (AS). Materials and Methods: Patients were enrolled in a prospective AS protocol at our institution between May 2005 and January 2016. Patients with SRMs ≤4 cm with serial cross‐sectional imaging available in‐house for review were included. Overall survival (OS) was estimated using the Kaplan–Meier method and modelled via Cox proportional hazards models. The primary endpoints analysed were the conditional probability of survival and tumour growth over time. Landmark analysis was used to evaluate survival outcomes beyond the 2‐year mark after the initial scan. The relative conditional survival of patients on AS was compared to those undergoing partial nephrectomy (PN) using inverse probability of treatment weighting. Results: A total of 272 patients were included in this analysis. The mean initial SRM size was 1.74 ± 0.77 cm, and the mean mass size closest to the 2‐year mark was 1.97 ± 0.83 cm. The likelihood of continued survival to 5 years improved after the 2‐year landmark. Patients with masses <3 cm who survived the first 2 years on AS had a 0.84–0.85 chance of surviving to 5 years, and if they survived 3 years, the probability of surviving to 5 years improved to 0.91. A slow tumour growth (β: 0.12; P < 0.001) with parallel growth rates was found for tumours <3 cm. Patients on AS and those who underwent PN had similar OS for ~7 years, beyond which PN demonstrated a trend of lower risk of death compared with AS (hazard ratio 0.57; P = 0.07). Conclusions: The conditional survival probability of patients with SRMs <3 cm on AS increased after 2 years. This information may prove useful to urologists and patients who are considering continuing AS vs intervention after the first 2 years on AS.